Efficacy of preprocedural mouth rinse containing chlorine dioxide in reduction of viable bacterial count in dental aerosols during ultrasonic scaling: A double-blind, placebo-controlled clinical trial - Rajiv Saini (Dental Hypotheses, 2015)
Background: The risk to dentists, dental assistants, and patients of infectious diseases through aerosols has long been recognized. The aim of this study was to evaluate and compare the efficacy of commercially available preprocedural mouthrinses containing 0.2% chlorhexidine (CHX) gluconate, chlorine dioxide (ClO 2 ) mouthwash, and water in reducing the levels of viable bacteria in aerosols. Materials and Methods: This single-center, double-blind, placebo-controlled, three-group parallel-designed study was conducted over a period of 4 months. One hundred twenty patients with chronic periodontitis were divided randomly into three groups (A, B, and C) of 40 patients each to receive the ClO 2 mouthwash, water, and 0.2% CHX gluconate respectively as preprocedural rinse. The aerosol produced by the ultrasonic unit was collected at five standardized locations with respect to the reference point, i.e., the mouth of the patient. The blood agar plates were incubated at 37°C for 48 h, and the total number of colony-forming units (CFUs) was counted and statistically analyzed. Results: The results showed that CFUs in groups A and C were significantly reduced compared to group B, and P < 0.001 [analysis of variance (ANOVA)]. CFUs in group C underwent the highest reduction, but statistically there was no significant difference between the mean values of postprocedural CFUs in groups C and A (i.e., P > 0.05). The numbers of CFUs were the highest at the patient′s chest area and lowest at the patient′s front i.e., the 6 o′clock position. Conclusion: This study proves that a regular preprocedural mouthrinse could significantly eliminate the majority of aerosols generated by the use of an ultrasonic unit, and that ClO 2 mouthrinse was found to be statistically equally effective in reducing the aerosol contamination to 0.2% CHX gluconate.